Changes in motivation and its relationship with academic performance among first-year chemical engineering students - Foong, Chan Choong (Elsevier B.V., 2022)
Lack of motivation is one of the grounds for dropouts among engineering students. Although developing students’ motivation is notable for its importance in engineering education, changes in students’ motivation over time have not been fully explored. By adopting Self-Determination Theory, this study examined the changes in engineering students’ motivation over six months and assessed the correlations between motivation and academic performance. A cohort of forty-six (n = 46) first-year chemical engineering students from a public university in Malaysia participated in this study. By using the Academic Motivation Scale, amotivation, extrinsic motivation, and intrinsic motivation of the students over six months were examined. In addition, correlations between motivation and academic performance were assessed. The students’ motivation generally remained unchanged after engaging in their studies for 6 months, except the extrinsic motivation – external regulation significantly increased. The students demonstrated the least amotivation, but they were most motivated “to have a good life later on”. The extrinsic motivation was significantly correlated with students’ first-semester academic performance while the intrinsic motivation – to experience stimulation was significantly correlated with students’ second-semester academic performance. First-year engineering students did not develop higher motivation after enroling in the programme, hence there is a need for motivation enhancement.